Phosphorus as a mitigator of the effects of water stress on the growth and photosynthetic capacity of tropical C-4 grasses - Kuwahara, Frank Akiyoshi [UNESP]; Souza, Gustavo Maia; Guidorizi, Kezia Aparecida; Costa, Ciniro [UNESP]; Lima Meirelles, Paulo Roberto de [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2016)
Water deficiency during the dry seasons influences the relationship between water and gas exchange in tropical grasses, reducing their productive potential. In addition, the phosphorus (P) deficiency Brazilian soils adds to the set of factors limiting crop production. In this context, the objective of this study was to evaluate the responses of different tropical forage species to phosphorus supplementation as mitigating the damage caused by water stress. Seeds of Urochloa brizantha cv. MG-4, Urochloa decumbens cv. Basilisk, Panicum maximum cv. Aries, Panicum maximum cv. Tanzania and Paspalum atratum cv. Pojuca were germinated in pots containing 10 liters of red-yellow Acrisol type soil. Experiments were conducted by combining levels of phosphorus, 8,0 and 100,0 mg of P dm(-3), with two irrigation regimes, 100 and 40% replacement of transpired water. The biometric parameters, photosynthetic capacity, leaf water potential and soil chemical characteristics were evaluated, and the data was submitted to analysis of variance (ANOVA, p < 0.05), and subsequently the means were compared using a Tukey test (p < 0.05). The results showed for tropical grasses grown under water stress, there is a clear mitigating effect of phosphorus supplementation, especially on the maintenance of biomass growth.
Keywords: pasture; leaf gas exchanges; fertilization; water deficit